Analisis Perbedaan Rasio Likuiditas dan Rasio Profitabilitas Sebagai Alat Ukur Kinerja Keuangan Antara Bank Konvensional dan Bank Syariah - Puspitaningrum, Ferry; Triyuwono, Iwan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2008)
Research aims at examining the liquidity and profitability of conventional and syariah banks. Research also observes the significant difference in the liquidity and profitability between conventional and syariah banks. Research subsumes into descriptive quantitative type. Data source results from bank's 2004-2006 financial statements. The data remain as secondary data collected from Indonesian Bank Library covering Bank Muamalat Indonesia, Bank Syariah Mandiri, Bank NISP, and Bank Panin. Data analysis concerns with financial ratio of each bank and compares this ratio with financial performance. The next step will be hypotheses testing with nonÂ¬parÂ« metric statistic tool, Mann-Whitney test. Results indicate that the significant difference emerges in the liquidity ratio between conventional and syariah banks. This difference involves quick ratio and loan deposit ratio. Profitability ratio of both banks doesn't differ significantly. Research also shows that much liquid loan in syariah bank don't mean that it increases the income of syariah bank. Keywords: liquidity ratio, profitability ratio, Mann-Whitney test